Same sex, different states : when same-sex marriages cross state lines - Koppelman, Andrew (Yale University Press, 2006)
Must a state in which gay marriage is not legal recognize such a marriage performed in another state? Most of the commonly offered answers are wrong. The Constitution does not require recognition in all cases, but it does forbid states from nullifying family relationships based in other states, or making themselves havens for people who are trying to escape obligations to their spouses and children. In this book, Andrew Koppelman offers workable legal solutions to the problems that arise when gay couples cross state borders. Drawing on historical precedents in which states held radically different moral views about marriage (such as marriages between kin, marriages involving very young individuals, and interracial marriages), Koppelman shows which state laws should govern in specific situations that today's gay couples may encounter as they travel or move from place to place. Americans are profoundly divided over same-sex marriage, and now that gay civil unions and marriages are legal in some states, the debates about what states can do have become increasingly urgent. Koppelman offers a sensible approach that will appeal to the best instincts of both sides.